Dynamic coronary roadmap-guided PCI reduces contrast volume and radiation time compared to standard angiography PCI: A meta-analysis - Mohammad Al Hayek; Ibrahem A. Beshr; Mohammed S. Beshr (Heliyon)
Background: Dynamic Coronary Roadmap (DCR) is a new PCI method that may reduce contrast dose and contrast-associated acute kidney injury (CA-AKI) risk. This paper evaluates DCR-guided PCI versus standard angiography PCI for contrast usage, procedure time, and CA-AKI risk. Methods: On May 1, 2024, we searched PubMed, Scopus, Embase, Cochrane Library, and clinicaltrials.gov for clinical trials or observational studies comparing DCR-guided PCI to standard angiography PCI. Outcomes were contrast media usage, radiation time, dose-area product, air kerma, radiation dose, post-PCI eGFR, AKI incidence, and procedure success. We used a random-effects model and analyzed outcomes using standardized mean difference (SMD) and odds ratio (OR). Results: Out of 1679 screened articles, only 5 were eligible, encompassing 941 patients. Findings show DCR-guided PCI significantly reduces contrast volume (SMD = −1.12, 95 % CI: 1.75 to −0.50, p = 0.0004), dose-area product (SMD = −0.71, 95 % CI: 1.25 to −0.17, p = 0.01), air kerma (SMD = −1.62, 95 % CI: 2.70 to −0.54), and radiation time (SMD = −0.75, 95 % CI: 1.32 to −0.18, p = 0.003) compared to standard angiography PCI. Despite lower incidence of acute kidney injury (AKI) in the DCR-guided PCI group, the odds ratio did not show statistical significance. Post-PCI eGFR also did not differ significantly between the two groups. Procedural success rates were similar, both exceeding 99 %. Conclusions: In this paper, we found that DCR-guided PCI is superior to conventional PCI in terms of contrast medium volume and radiation time. Future randomized controlled trials with larger sample sizes are needed to confirm these findings, especially in patients with kidney disease.